Efeitos da potencialização pós-ativação induzida por nado com paraquedas no desempenho e técnica de nado em prova de 50 metros nado crawl - Bufalo, Santiago Soares (2022)
Powerful muscle actions can be potentiated following pre-conditioning exercise consisting of near-maximal contractions. The ensuing enhancement in explosive actions is termed post-activation potentiation (PAP). In swimming, the race that relies the most on powerful muscle actions is the 50-meter front crawl. The aim of the present study is to investigate the impact of a warm-up protocol consisting of swimming attached to a parachute in 50-meter front crawl performance. Three healthy regional-level swimmers (minimum performance index: 28 seconds) participated in the study. Swimmers performed two different warm-up protocols, control and PAPE, on the same day, with a 30-minute interval between protocols, in a randomized manner. For the control warm-up, participants swam approximately 600 meters, with 500 m crawl at low intensity followed by 4 sprints of 10 s maximum crawls. In the PAPE condition, the swimmers performed a warm-up consisting of a 500 m crawl at low intensity followed by a 2-minute break and 4 maximum sprints of 10 s freestyle crawl efforts with a parachute attached to their waists interspersed by 1-minute rests. Six minutes after both warm-up protocols, participants completed a maximum 50-meter sprint. The swimmers' performance was measured by means of the duration of the 50 m freestyle shot, and two cameras were used to film the shot and subsequent analysis of the swimming technique (stroke frequency and coordination index). It was possible to notice an improvement of 1.5 ± 2.9% in the 50 m times between conditions (27.88 ± 0.25 s vs 27.45 ± 0.55 s for the control and PAPE conditions, respectively). Still, comparing the test partials, the PAPE condition presented better times in both partials.